The Influence of Information Technology On Religious Practices In Urban Muslim Communities - Jaenudin, Agung (Al-madinah: Journal of Islamic Civilization, 2024)
This study aims to analyze the influence of information technology on religious practices in urban Muslim communities. With technological advances such as the internet, religious applications, and social media, access to information and the implementation of worship have become easier and more efficient. This study uses descriptive qualitative methods to delve deeply into how technology affects the way urban Muslims carry out their daily worship. Data is collected from various secondary sources such as articles, books, and related journals. The results of the study show that information technology makes it easier for Muslims to carry out worship and deepen religious knowledge flexibly, but it also poses challenges such as individualization of worship and fragmentation of religious understanding. Therefore, a balance between the use of technology and involvement in religious activities is collectively needed to maintain spiritual and social values in the religious practices of urban Muslim communities.